Analisis Optimalisasi Kinerja Keuangan Pada Usaha Agen Kembang Jagung di Desa Pukem, Sukadana - Lilih Rahmawati; Al Tiyas Fitriani; Rosa Liana; Rindy Astrid Ramadhani; Carmidah Carmidah (International Forum of Researchers and Lecturers, 2024)
The background of this research is about optimizing company assets and limited resources in company operations. The aim is to find out whether the financial performance of the Cornflower Agent business is optimal or not. The method used in this research is qualitative method. The data used are primary data and secondary data. With this data, researchers can find out what types of fixed assets are used by Cornflower Agents, namely buildings, machines and vehicles. The limited resources in the Cornflower Agent business are human resources, because they have been replaced by machines that can make the grinding process easier.